A 4D printing strategy and integrated design for programmable electroactive shape-color double-responsive bionic functions. (26th May 2021) - Chen, Daobing; Liu, Qingping; Geng, Peng; Tang, Sihan; Zhang, Junqiu; Wen, Shifeng; Zhou, Yan; Yan, Chunze; Han, Zhiwu; Shi, Yusheng
Graphical abstract: A multi-material 4D printing programmable electroactive shape-color dual-response strategy were reported. The shape-color dual-response is controlled by the electricity, thus, making the shape-color dual-response devices more concise, efficient and programmable. A variety of bionic functions are realized, including biomimetic mimosa leaf closing in turn, biomimetic starfish area changing color, and biomimetic shape-color dual-changing wings. Image 1 Abstract: The extraordinary potential of 4D printing regarding shape-changing, property-changing and functionality-changing could be widely utilized in the biomedical, aerospace, and robotics fields. Shape-color double-responsive 4D printing further expands the connotation of 4D printing by integrating both shape-changing and visual-changing, thereby providing new ideas and methods for actualizing active functions. However, current shape-color double-responsive 4D printing utilizes an external heat source, which is a sizeable limitation for actualizing the programmable shape-color dual-response function. Here, to overcome this issue, an electroactive shape-changing material, and thermal shape-color dual-response material are prepared, integrated, and printed with a double-nozzle multi-material printer. After preparing the materials, programmable electrothermal effects in different regions are actualized by controlling their resistances. Furthermore, multi-material printing allows for electroactive shape-changing materials to be embedded into thermal shape-color dual-response materials, thus actualizing programmable electroactive shape-color double-responsive 4D printing. This ingenious design concept and high-performance materials involved are demonstrated by mimicking biological functions such as mimosa leaves closing in turn, colorful starfish, and shape-color dual-changing wings. This study paves the way for development of programmable multi-functionality actuators with simultaneous fast responses and easy-fabrication for utilization in promising applications on biomedical devices and bioinspired robotics.